2017
DOI: 10.4274/tdd.3239
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pruritus and Pain on the Quality of Life

Abstract: Kaşıntı ve Ağrının Yaşam Kalitesi Üzerine EtkisiThe Effect of Pruritus and Pain on the Quality of Life Öz AbstractObjective: Pruritus and pain are disturbing symptoms. They display similar pathogenetic and clinical characteristics and affect the quality of life significantly. However, it is unknown which affects the quality of life more adversely. Our aim is to determine which of the symptoms of pruritus and pain affects the quality of life more in negative way. Methods: Fifty patients with functional pruritus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Other studies have also showed that in adults with atopic dermatitis, difficulty falling asleep and decreased sleep duration due to low sleep quality cause them to experience daytime sleepiness, fatigue and dysfunction [10 and 17]. In their study of the effect of itching and pain on the quality of life, Atış et al, (2017) found that sleep was an important component of the physical activity [18]. In another study, pruritic episodes in functional pruritus were reported to occur during sleep [19].…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Other studies have also showed that in adults with atopic dermatitis, difficulty falling asleep and decreased sleep duration due to low sleep quality cause them to experience daytime sleepiness, fatigue and dysfunction [10 and 17]. In their study of the effect of itching and pain on the quality of life, Atış et al, (2017) found that sleep was an important component of the physical activity [18]. In another study, pruritic episodes in functional pruritus were reported to occur during sleep [19].…”
Section: Findings and Discussionmentioning
confidence: 99%